2010
DOI: 10.1088/0957-0233/22/2/024001
|View full text |Cite
|
Sign up to set email alerts
|

Scanning probe microscope dimensional metrology at NIST

Abstract: Scanning probe microscope (SPM) dimensional metrology efforts at the US National Institute of Standards and Technology (NIST) are reviewed in this paper. The main SPM instruments for realizing the International System of Units (SI) are the Molecular Measuring Machine, the calibrated atomic force microscope and the critical dimension atomic force microscope. These are optimized for long-distance measurements, three-dimensional measurements over conventional SPM distances and critical dimension or linewidth meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…1, which defines the coordinate system of the instrument. Experience in characterizing mSPMs at other metrology institutes [4][5][6][7][8][9] has shown that the metrological frame is the dominant source of measurement uncertainties arising from alignment errors, particularly Abbé errors and nonorthogonality of the measurement axes, and environmental vibration. To achieve the target total uncertainty of dimensional measurements, minimizing these contributions is a principal consideration in the design of the metrological frame and the material selected for its construction.…”
Section: System Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…1, which defines the coordinate system of the instrument. Experience in characterizing mSPMs at other metrology institutes [4][5][6][7][8][9] has shown that the metrological frame is the dominant source of measurement uncertainties arising from alignment errors, particularly Abbé errors and nonorthogonality of the measurement axes, and environmental vibration. To achieve the target total uncertainty of dimensional measurements, minimizing these contributions is a principal consideration in the design of the metrological frame and the material selected for its construction.…”
Section: System Integrationmentioning
confidence: 99%
“…1,2 The challenge in realizing this mSPM concept is to create a macroscopic mechanical instrument capable of traceable dimensional measurement at the nanoscale with a combined uncertainty of less than 1 nm. Experience in designing ultraprecision mechanical stages and instruments 3 and in operating similar mSPMs at other metrology institutes [4][5][6][7][8][9] has shown that there are many contributions to the uncertainty of the displacement measurements. These include alignment errors (particularly Abbé errors 10 ), deformations of the mechanical structures (for instance, due to thermal expansion), motion errors of the translation stage, form errors of the interferometer mirrors, nonlinearities of the interferometers, and fluctuations in the refractive index of air.…”
Section: Introductionmentioning
confidence: 99%
“…It is intended primarily to calibrate physical standards for other AFMs. The design, performance, and uncertainties of the system have been discussed elsewhere [1,[4][5][6]. The C-AFM has metrology traceability to the SI meter in all three axes via the 633 nm wavelength of an I 2 -stabilized He-Ne laser.…”
Section: The Nist Calibrated Atomic Force Microscope (C-afm)mentioning
confidence: 99%
“…Several laboratories and national metrology institutes (NMIs) have developed their own mAFMs, all these characterized by their on-board metrology systems and opto-mechanical set-ups [1][2][3][4][5][6][7][8][9][10]. These instruments make use of different arrangements and selected materials aiming at a good compromise between working volume, metrology loop, stiffness and overall thermal stability.…”
Section: Introductionmentioning
confidence: 99%